2022
DOI: 10.1097/rli.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Media Reduction in Computed Tomography With Deep Learning Using a Generative Adversarial Network in an Experimental Animal Study

Abstract: Objective: This feasibility study aimed to use optimized virtual contrast enhancement through generative adversarial networks (GAN) to reduce the dose of iodinebased contrast medium (CM) during abdominal computed tomography (CT) in a large animal model. Methods: Multiphasic abdominal low-kilovolt CTs (90 kV) with low (low CM, 105 mgl/kg) and normal contrast media doses (normal CM, 350 mgl/kg) were performed with 20 healthy Göttingen minipigs on 3 separate occasions for a total of 120 examinations. These includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The percentage is rather high, and it could be significantly reduced using more sophisticated coregistration techniques that are already part of the state of the art but are not object of the present study. A potential solution to work around the misalignment of images applied for training has been proposed by Haubold et al, 53 where the CycleGAN architecture is applied to abdominal computed tomography in a large animal model. Since CycleGAN loss does not contain any pixelwise computation, the training is not affected by coregistration imperfections.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage is rather high, and it could be significantly reduced using more sophisticated coregistration techniques that are already part of the state of the art but are not object of the present study. A potential solution to work around the misalignment of images applied for training has been proposed by Haubold et al, 53 where the CycleGAN architecture is applied to abdominal computed tomography in a large animal model. Since CycleGAN loss does not contain any pixelwise computation, the training is not affected by coregistration imperfections.…”
Section: Discussionmentioning
confidence: 99%
“…For each examination, it was possible to zoom and window without restrictions. Subsequently, the radiologists had to select the side on which the true normal-dose sequence is shown, and they had to evaluate whether the 2 representations have consistent findings according to the preliminary work of Haubold et al 13,14 This was an additional quality assurance step to ensure that the network does not change the image in an unexpected way. This includes changes in anatomy as well as image artifacts that can simulate a pathology.…”
Section: Qualitative Image Evaluationmentioning
confidence: 99%
“…Recently, however, a systematic intraindividual analysis in pigs has shown that a reduction of the GBCA dose of the venous phase by 40% and of up to 60% of the arterial phase in time-resolved magnetic resonance angiography (MRA) is possible while preserving the delineation of small vessels 12 . Furthermore, in recent years, due to technical progress in the field of machine learning, new methods for reducing the amount of contrast media in CT 13,14 or generating a synthetic MRA 15 have been demonstrated. In addition, various algorithms have been developed to generate a late contrast phase in MRI of the brain from noncontrast data 16 or from low-dose data using split-dose protocols 17,18 .…”
mentioning
confidence: 99%
“…Since then, others have demonstrated the ability of GANs to synthesize realistic virtual contrast enhanced images, 24,25 potentially reducing the contrast media dose required for effective contrast enhanced imaging. 26,27 Beyond the previously described challenges associated with contrast enhanced imaging, there may be situations during imaging that result in poor contrast media uptake, either from compromised kidney function, degree of compliance with established scanning protocols, or other situation specific complications (e.g. corticomedullary and/or nephrogenic phase scanning occurs too early or too late and times of peak image contrast are missed) which could reduce CNN-based kidney segmentation performance if the CNN is trained only on high quality contrast enhanced images.…”
Section: Introductionmentioning
confidence: 99%